RESPONSIBILITAS PEMERINTAH KABUAPTEN SIAK TERHADAP PENCEMARAN UDARA DI KECAMATAN TUALANG TAHUN 2014-2015 (DESA PINANG SEBATANG TIMUR) - Alharoma Amnur; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
One of the negative impacts of the rapid growth of industry in the district of Tualang the environmental pollution, especially air pollution resulting from the rest of the business, and one of the businesses or large companies in the District Tualang Siak. One of the villages located close to major industrial companies are Pinang Sebatang Timur Village. The formulation of the problem in this study as to how responsibility Siak District government against Air Pollution in Sub Tualang especially in the Pinang Sebatang Timur Village. This study aims to determine the efforts made by the government of Siak in addressing the problem of air pollution caused by the company or factory in the Pinang Sebatang Timur Village District of Tualang. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Based on the findings, it seemed responsibility the implementation of control activities undertaken by the Environment Agency (BLH) Siak against air pollution have been good, but not optimally. Because the control activities against air pollution carried Environment Agency (BLH) Siak there are problems that the lack of supervision and control carried Environment Agency (BLH), only 2 times a year and less to promote the public about the importance of awareness of preserving the environment especially those located around the industrial companies in Siak. Air pollution control strategies can be done by increasing the inventory and identification of sources of air pollution, improving waste management, establish pollution load capacity, increase knowledge and participation in submitting complaints, increasing supervision of the activity of air pollution. Keywords: Strategic Management, Responsibility, Air Pollution